KODE ETIK DAN TATA LAKU DALAM MENJAGA EKSISTENSI AKUNTAN (STUDI PADA SAUNG ANGKLUNG UDJO) - Susana Dewi; Karsam Karsam; Erfan Erfiansyah (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2022)
The industrial revolution 4.0 and Society 5.0 affects all aspects of the order of life, which causes the accounting profession to carry out transformations but still uphold the code of conduct and professionalism. This study aims to determine the ethics in the accounting profession's behavior in carrying out the transformation to the Industrial Revolution 4.0 and the Era of Society 5.0. Methods This research uses a qualitative study approach with an interpretive paradigm. The sample in this study was Saung Angklung Udjo-Bandung, West Java, which was held in early November 2021. The data was obtained by interviewing sources from the PR/Marketing, the Production and Warehouse, and the Art Performance Department. The results showed that the pamali culture in Saung Angklung Udjo as a Sundanese cultural heritage is still very strong, especially in the manufacture of angklung and the selection of raw materials, the behavior in playing the art of angklung to face the socialites of the changes in the era of the industrial revolution 4.0 towards the era of sosiety 5.0, Saung Angklung Udjo must do digital transformation, this is in line with the role of accountants in the pandemic era in order to pass the industrial era 4.0 to welcome the era of society 5.0, it is necessary to transform in various fields but still uphold the code of ethics and professionalism of accountants. By carrying out the transformation, accountants should be able to reduce deviations from the code of conduct by complying with the code of ethics, among others; Professional Responsibility, Public Interest, Integrity, Objectivity, Professional Competence and Due Care, Confidentiality, Professional Conduct and Technical Standards. This study learns more about the transformation of accountants by maintaining a pamali culture or code of ethics, code of conduct and professionalism of accountants in dealing with the socialites of the industrial revolution 4.0 towards the era of society 5.0.